Changes of Self-Rated Health Status, Overweight and Physical Activity During Childhood and Adolescence—The Ratchet Effect of High Parental Socioeconomic Status - Rittsteiger, Lea; Hinz, Thomas; Oriwol, Doris; Wäsche, Hagen; Schmidt, Steffen; Kolb, Simon; Woll, Alexander (Frontiers in Sports and Active Living, 2022)
Childhood and adolescence are important life periods for the development of health status and physical activity (PA) behaviours. This study analyses the stability and potential changes of self-rated health status, overweight and PA behaviour over time, specifically focusing on the age and the socioeconomic status of children and adolescents. We employ representative longitudinal data for German children and adolescents from the Motorik-Modul Study and the German Health Interview and Examination Survey. Using four different dichotomous health status and PA indicators (self-rated health status [SRHS]; overweight; moderate-to-vigorous PA; and leisure sports engagement), we report within-person transition rates across the panel waves when the survey was taken (2003–2006, 2009–2012, and 2014–2017). Additionally, we report results of logistic regressions estimating the impact of children's age, gender, migration background, and their parents' socioeconomic status on these transition rates. The transition rates show mixed results. While children and adolescents from highly problematic states reporting bad SRHS and no leisure sports engagement at an early stage tend to improve later on, overweight children mostly stay overweight. Age and social inequality indicators correlate with some of the chances of improving or worsening the health and PA states. Most clearly, high parental status prevents the health status and PA from worsening over all transitions, particularly becoming overweight, representing a ratchet effect. The results of the present study underline that health policy needs to target specific groups to reduce social inequality in the health status and PA of children and adolescents.